Rock Island requiem : the collapse of a mighty fine line - Schneider, Gregory L., 1965- (University Press of Kansas, 2013)
Chronicles the unraveling and demise of the mighty Rock Island Railroad--the largest railroad liquidation in American history. Victim of government regulation, inept management, individual greed, and self-interest, its downfall presents in microcosm the story of the railroad industry's larger problems in postwar America--and in relief, the story of America's economic failures in the 1960s and 1970s.